The contribution of lower torso, upper torso and upper limbs segmental motion to hammer head velocity during acceleration phase - Fujii, H.; Byun, K.; Ogata, M.; Fujii, N. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
In hammer throw event, the distance of the hammer throw is mainly determined by hammer head resultant velocity at release. During turn phase, hammer head resultant velocity is increased gradually with four turns and is increased during double support phase. The purpose of this study was to investigate the contribution of the motions in the lower torso, upper torso, upper limbs and hammer segment to the hammer head tangential velocity during double support phase.